2021
DOI: 10.1021/acs.joc.1c02020
|View full text |Cite
|
Sign up to set email alerts
|

Clausanisumine, a Prenylated Bicarbazole Alkaloid from the Fruits of Clausena anisum-olens and Its Potential Anti-HIV Activity

Abstract: A unique prenylated bicarbazole alkaloid, clausanisumine (1), and two biogenetically related known monomer carbazole alkaloids, mukonal (2) and 3-methylcarbazole (3), were isolated from the fruits of Clausena anisum-olens. Clausanisumine (1) was an uncommon prenylated bicarbazole alkaloid, possessing an unprecedented carbon skeleton, which was composed of a simple carbazole alkaloid and a prenylated carbazole alkaloid. The chemical structure of 1 was established by a combination of comprehensive spectral metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 24 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…Structures of the phyto-carbazole alkaloids isolated from various Clausena species with potential neuroprotective effects against NDs are presented in Figure 3. Phytocarbazole alkaloid clausenanisines A-F and clausevestines were isolated from the fruits of C. anisumolens [56] and from the stem and leaves of C. vestita [57], respectively. Various prenylated carbazole alkaloids presented a significant inhibition (IC 50 0.63-8.3 µM) of NO production in mouse macrophage RAW 264.7 cells by LPS induction, with hydrocortisone (IC 50 3.8 µM) as the positive control [57,58].…”
Section: Phyto-carbazole Alkaloids From the Genus Clausenamentioning
confidence: 99%
“…Structures of the phyto-carbazole alkaloids isolated from various Clausena species with potential neuroprotective effects against NDs are presented in Figure 3. Phytocarbazole alkaloid clausenanisines A-F and clausevestines were isolated from the fruits of C. anisumolens [56] and from the stem and leaves of C. vestita [57], respectively. Various prenylated carbazole alkaloids presented a significant inhibition (IC 50 0.63-8.3 µM) of NO production in mouse macrophage RAW 264.7 cells by LPS induction, with hydrocortisone (IC 50 3.8 µM) as the positive control [57,58].…”
Section: Phyto-carbazole Alkaloids From the Genus Clausenamentioning
confidence: 99%
“…Our preliminary experimental results revealed that the 85% ethanol extract of the stems and leaves of C. cochinchinense showed notable inhibitory effect against nitric oxide (NO) production induced by lipopolysaccharide in mouse macrophage RAW 264.7 cells with an IC 50 value of 9.68 ± 0.12 μg/mL in vitro, as well as anti-HIV-1 reverse transcriptase (RT) effect with an EC 50 value of 7.19 μg/mL. To fully explore the enormous potential of Hainan’s unique tropical medicinal plants and tropical fruits in the prevention and treatment of major human diseases, in the course of our continuing investigation of biologically active and structurally diverse natural products from the tropical medicinal plants and tropical fruits [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ], a phytochemical study on the stems and leaves of C. cochinchinense was thus undertaken and led to the isolation and characterization of four new xanthones, cratocochinones A–D ( 1 – 4 ),which are a kind of rare natural product with extensive biological activities [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ], alongside eight known analogues 5 – 12 . Their chemical structures were determined on the basis of comprehensive spectral analyses.…”
Section: Introductionmentioning
confidence: 99%